Graphene-integrated mesh electronics with converged multifunctionality for tracking multimodal excitation-contraction dynamics in cardiac microtissues - Gao, Hongyan; Wang, Zhien; Yang, Feiyu; Wang, Xiaoyu; Wang, Siqi; Zhang, Quan; Liu, Xiaomeng; Sun, Yubing; Kong, Jing; Yao, Jun (Nature communications, 2024)
Cardiac microtissues provide a promising platform for disease modeling and developmental studies, which require the close monitoring of the multimodal excitation-contraction dynamics. However, no existing assessing tool can track these multimodal dynamics across the live tissue. We develop a tissue-like mesh bioelectronic system to track these multimodal dynamics. The mesh system has tissue-level softness and cell-level dimensions to enable stable embedment in the tissue. It is integrated with an array of graphene sensors, which uniquely converges both bioelectrical and biomechanical sensing functionalities in one device. The system achieves stable tracking of the excitation-contraction dynamics across the tissue and throughout the developmental process, offering comprehensive assessments for tissue maturation, drug effects, and disease modeling. It holds the promise to provide more accurate quantification of the functional, developmental, and pathophysiological states in cardiac tissues, creating an instrumental tool for improving tissue engineering and studies. Tracking electrical and mechanical activity in in-vitro cardiac microtissues is challenging. Here, authors develop tissue-like electronics that can ‘grow’ with the cardiac microtissues and realize the simultaneous tracking of both signals.